A Cold Environment Aggravates Cough Hyperreactivity in Guinea Pigs With Cough by Activating the TRPA1 Signaling Pathway in Skin - Dong, Ran; Zhang, Tongyangzi; Wei, Weili; Zhang, Mengru; Chen, Qiang; Xu, Xianghuai; Yu, Li; Qiu, Zhongmin (Frontiers in Physiology, 2020)
Cough exacerbation in cold environments is a characteristic feature of patients with chronic cough. The general consensus that inhalation of cold air stimulates cough receptors is not consistent with the fact that cold air is usually unable to enter the lower airway directly. To elucidate the effects of cold environments and transient receptor potential ankyrin 1 (TRPA1) on cough, we compared cough reactivity, airway inflammation, and TRPA1 expression in guinea pigs with chronic cough induced by the repeated inhalation of citric acid for 15 days. The guinea pigs were exposed to cold environments for three consecutive days, from the 13th of 15 days. Repeated inhalation of citric acid increased cough reactivity to inhaled cinnamaldehyde. Exposure to cold environments further aggravated cough hyperreactivity only in guinea pigs with chronic cough, but not in normal guinea pigs. Cough hyperreactivity was promoted when the whole body and trunk-limbs, but not the heads of the guinea pigs were exposed to cold environments, and abolished by pretreating the skin through immersion in the TRPA1 antagonist, HC-030031. Similarly, substance P levels in bronchoalveolar lavage fluid, and TRPA1 expression in the trachea and skin, were increased in guinea pigs with the whole body and trunk-limbs, rather than the head, exposed to cold environments. However, this trend was also abolished by pretreatment of the skin via immersion in HC-030031. Similar changes in TRPA1 expression were also detected in the sensory fibers of the trachea and skin, as identified by immunofluorescence and laser-scanning confocal microscopy analysis. These results suggest that exaggerated cough hyperreactivity induced by cold environments may be related to activation of the cold-sensing TRPA1 signaling pathway in the skin, rather than the inhalation of cold air.